Eminence or evidence based dentistry ....... whither Homo evidensis? - Zbys Fedorowicz; James V. Keenan (Universidade Estadual de Campinas, 2015)
In the past it was recognized that dentistry and its coassociates fear and pain tended to foster role-dominance by the clinician. So in this new era of patient focused care should we not attempt to make use of transactional exchanges of information, whichplace us firmly on the road to that somewhat futuristic goal of a partnership in oral health? The future of EBD predicates that decision-making will no longer be the prerogative of administrator or clinician. Evidence will be 'king', the patient will move from passive to active role and will, like any other 'customer' demand decision-making information based on all the evidence available. Additionally, for the effective practice of EBD, it will be vital for the clinician to acquire all necessary skills to enable him to adapt to a patient preferred level of involvement in decision-making. Thus the future of EBD will be part of a challenge of individualizing care based on best evidence, clinical judgment and user preferences. In 1890G.V.Black proposed a classification of cavity design which has untilrecently stood the test of time, it is hoped that the involvement of Homo Evidensis in EBD has a more accelerated tempo. (Endnotes)